Predicting intercrop competition, facilitation, and productivity from simple functional traits - MacLaren, C.; Waswa, W.; Aliyu, K.T.; Claessens, Lieven; Mead, A.; Schöb, C.; Vanlauwe, Bernard; Storkey, J. (Elsevier, 2023)
Context Recent meta-analyses demonstrate that intercropping can increase the land use efficiency of crop production by 20–30 % on average, indicating a strong potential contribution to sustainable intensification. However, there is substantial variability around this average: individual studies range from half to double the land productivity of monocrops. Legume-cereal intercrops and intercrops with high temporal niche separation tend to be more productive than the average, but these two combination types are not always suitable. There is a need to explore other possibilities to achieve productive intercrops.